(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Urbanization is the part of development, which define the population dynamics over different places on earth. Urbanization as a process of concentration has socio-economic relevance in spatio-temporal dimensions. Urbanization visualizes the change in not only the birth places of civilizations (river plains) but with the stance of time it is visible in mountainous areas. In this context the present paper tries to show the spatial pattern in the level of urbanization in North-East India. This paper also tries analyzing the changing pattern of urbanization from 2001 to 2011. The study is based on secondary data compiled and availed by Census of India. To achieve the objective of the study, the share of urban population has been calculated for both 2001 and 2011 year. To look over the approach of the urban area service, the rural areas and population served by the urban centers has been intended. Maximum distance to nearest urban center also has been calculated to analyze the spatial impact of urbanization. The method of Z score has been used to look-over the overall level of urbanization in different districts of North-East India. The result has been found the low level of urbanization. Share of urban population in NE India has increased from 23.39 in 2001 to 27.64 in 2011 which is only 4 percent and below the national average i.e. 31.16 percent. Up to Class-3, few towns have increased as compare to 2001 but the percentage to total population decreased. This is because of the Class-4, 5 and 6 cities, has almost double the towns in 2011 and their percentage to total population has increased.